Ibrahim Yaacob writing against imperialism - Mohd Noor Merican, Ahmad Murad (Melaka Hari Ini Sdn. Bhd., 2020)
Ibrahim Yaacob’s 1941 Melihat Tanah Air is a futurist document of the nation. To him, the Malay Archipelago’s location then described as the east (dunia timur) holds the key to the Pacific Ocean and the world economy.